Cumulative Disadvantage and Health: Long-Term Consequences of Obesity? - Ferraro, Kenneth F.; Kelley-Moore, Jessica A. (American Sociological Review, 2003)
Drawing from cumulative disadvantage theory, the health consequences of obesity are considered in light of the accumulation of risk factors over the life course. Two forms of compensation are also examined to determine if the risk due to obesity is persistent or modifiable. Analyses make use of data from a national survey to examine the consequences of obesity on disability among respondents 45 years of age or older, tracked across 20 years (N = 4,106). Results from tobit models indicate that obesity, especially when experienced early in life, is consistently related to lower-body disability. The results also show that obesity has long-term health consequences during adulthood, altering the life course in an enduring way. Compensation was not manifest from risk-factor elimination (weight loss), but rather through regular exercise. Although there is evidence for long-term consequences of risk factors on health, the findings suggest that more attention should be given to compensatory mechanisms in the development of cumulative disadvantage theory.